Mahar Unik Dan Mahar Bernilai Fantastis Dalam Perspektif Fikih Munakahat - Nihayati, Dini Arifah (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
The trend of unique dowry and fantastic dowry is mushrooming. Islam, does not specify the minimum and maximum dowry value. However, this trend seems to be a gap when it clashes with the public mindset that low dowry is identified with a lack of respect for women, while high dowries are considered difficult for men. Between the two, Indonesian people are used to following the dowry standards that apply in society to carry out the marriage contract. The mindset that collides with reality raises questions about the sharia and the law of giving dowry in various nominal or forms. Therefore, the authors need to examine this trend, especially its implications for the marriage contract. the author chooses fiqh munakahat as a knife of analysis. Because fiqh munakahat regulates the laws relating to marriage in Islam. This research is expected to be able to develop the application of fiqh munakahat to the unique and fantastic dowry trend. The author reaches the conclusion that in the perspective of munakahat fiqh, dowry can be given in any form and in unlimited value as long as the dowry meets the requirements. Unique or fantastic dowry does not affect the status of the marriage contract.